1977
DOI: 10.1111/j.1745-4549.1977.tb00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tomato Condition in Bin Loads of Processing Tomatoes Harvested at Different Levels of Ripeness

Abstract: VF145‐7879 variety of tomatoes were commercially machine harvested at three maturity levels which were 12 days and 7 days before the field was to be customarily harvested, and again when the field was harvested for delivery to the processor. The effects of transportation, storage and a simulated commercial wash were measured in terms of wholeness, several degrees of damage, and loss by weight for each of the maturity levels. Tomatoes harvested at the regular time showed greater losses and deterioration of cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

1977
1977
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
1
4
1
Order By: Relevance
“…The dry matter contents less than or equal to 5% (from 3.63 to 5.67%) for all fruits are below the theoretical value of more than 5%, retained by Fagbohoun& Kiki [25].However, these dry matter contents obtained for these fruits are similar to the results of Dossou et al [26].who obtained 4 to 5% dry matter in their study in Benin.…”
Section: Discussionsupporting
confidence: 76%
“…The dry matter contents less than or equal to 5% (from 3.63 to 5.67%) for all fruits are below the theoretical value of more than 5%, retained by Fagbohoun& Kiki [25].However, these dry matter contents obtained for these fruits are similar to the results of Dossou et al [26].who obtained 4 to 5% dry matter in their study in Benin.…”
Section: Discussionsupporting
confidence: 76%
“…The systems approach subdivides the postharvest handling system into recognizable components and studies the effects of and interrelationship between these components ). Systems approaches have been developed to asses damage (Allen and O'Brien 1977;Leonard et al 1977;O'Brien et al 1978;Aworh er al. 1983;Shewfelt et al 1985a;Campbell er al.…”
Section: Qurrlity -Ementioning
confidence: 99%
“…1978;Hood et af. 1981;Shewfelt et al 1987a), pimiento peppers (Shewfelt et al 1985a) and tomatoes (Allen and O'Brien 1977;Leonard et al 1977;Mongelli 1980;Apolinario ef al. 1984;Jordan et af.…”
Section: Qurrlity -Ementioning
confidence: 99%
“…Severe damage exists when large cracks or splits extend through the wall and expose the seed locules. The percentage of tomatoes with visible locules prior to washing at the processing plant can be used to predict the percentage of weight loss through the washing operation (31). This weight loss is largely due to the loss of contents from the seed locules.…”
Section: Processing Tomatoesmentioning
confidence: 99%
“…Studies by Ries and Stout (43) have shown that handling tomatoes in bulk containers results in more damage than does handling in lug boxes. The amount of damage increases with increasing fruit depth and is reflected by an increase in the percentage of fruit with visible seed locules (31,40). Small cracks in the tomatoes which may exist after filling into the container become progressively larger during transport to the processing plant.…”
Section: Processing Tomatoesmentioning
confidence: 99%